Analisis Intellectual Capital dan Relationship Satisfaction Terhadap Business Performance: Studi UMKM Rumah Makan Nasi Padang di Kota Sukabumi - Nabila Maulana Yusup, Silva; R Deni Muhammad Danial; Nor Norisanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Micro, Small and Medium Enterprises or what are often called UMKM support 60% of the Indonesian economy. Sukabumi is an area that has 57,319 UMKM, one of which is Padang rice restaurant UMKM. Nasi Padang restaurant UMKM is Padang or Minangkabau cuisine, a cultural heritage from generation to generation, maintaining the authenticity of the tastes of the past as a regional identity that has problems with business performance as well as intellectual capital and relationship satisfaction. The aim of this research is to find out how intellectual capital and relationship satisfaction influence the business performance of UMKM at Nasi Padang restaurants in the city of Sukabumi. The population in this study were UMKM Padang rice restaurants in the city of Sukabumi. The method used is a quantitative method with an associative descriptive approach. With a total sample of 51 with saturated sampling. The statistical results of the f test (simultaneous) show a simultaneous and significant influence of the intellectual capital and relationship satisfaction variables on business performance. Based on the statistical results of the t test (partial test), intellectual capital has a negative and insignificant effect on business performance. Meanwhile, relationship satisfaction has a positive and significant effect on business performance.